Implementasi Algoritma Set Partitioning in Hierarchical Trees (SPIHT) dan Algoritma Huffman Untuk Kompresi File Citra - Lubis Irsan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
As technology develops, the process of sending files no longer needs to be done manually. Data or files can be sent electronically via email. The image file size is sometimes very large, where the better the quality of the resulting image, the bigger the pixel size needed to record the image. With a very large image file size, the transfer process may fail, because the media storage space exceeds its limit. The solution to this problem is how the image file can be compressed in order to speed up the transfer and storage of image files. Image compression is done by reducing the size of the image file by reducing the bits in the image file, but not eliminating the information data in it. By compressing, large data will be reduced in size so as to save storage space. In this study, the algorithm used is the Swiss army knife data compression, using this method, the compression results from the value of k have different compression results for each value, and the compression results will be beneficial in sending and moving image files more easily